The Impact of Zoroastrianism on Mala Khalil Mshakhti’s Poetry - Khelil, kameran (Humanities Journal of University of Zakho, 2021)
Before the emergence of Islamic Religion, Zoroastrianism was the religion of Kurds, after Islamic religion the Zoroastrianism religion is decreased and gets lost, but at the same time it is remained variously in the culture and literature of Kurdish people as well as there is still its impact on them particularly after uprisings and developing of Kurdish nationalism by the late of nineteenth century and during the 20th century. In this period, the Zoroastrianism religion is identified in a modern way in the Kurdish culture and literature. The importance and dealing with this religion becomes a part of the nationalism, there are numerous writers and poets proudly dealt with the Zoroaster and Zoroastrianism. One of that poets is Mala Khalil Mishakhti who is highly impressed by that religion which is Zoroastrianism, but, the difference between Mshakhti and all other poets is that Mishakhti became familiar with the Zoroastrianism and the tradition due to his direct interaction with the society while in Immigration in Iran and he widely examined the aspect of Zoroastrian People along with the religion. This study is an attempt to figure out the way how Mshakhti was influenced by the Zoroastrianism and his interaction with the people. The study is conducted by a hypothesis that Mshakhti’s Influence by Zoroastrianism was mostly nationalistic, his admiration towards that religion was not only a strong desire, but, it was the results of his reading and researching of that religion itself. This study is obviously accomplished based on the descriptive analysis approach.